2008
DOI: 10.1111/j.1440-1827.2007.02199.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune pancreatitis‐associated prostatitis: Distinct clinicopathological entity

Abstract: Autoimmune pancreatitis (AIP) has been recently proposed as a disease entity, and an elevated serum IgG4 level is a characteristic finding in it. This disease is sometimes associated with other inflammatory diseases, such as retroperitoneal fibrosis and sclerosing cholangitis. To elucidate the clinicopathological characteristics of AIP-associated prostatitis (AIP-P), the clinicopathological findings of AIP-P patients were evaluated, and the immunohistochemical expression of the IgG subclasses (IgG1, IgG2, IgG3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 34 publications
1
66
0
3
Order By: Relevance
“…This disease has only been recently proposed and is considered to involve systemic inflammatory fibrosis, including retroperitoneal fibrosis, autoimmune pancreatitis, chronic sclerosing sialadenitis and sclerosing cholangitis [1,2,3,4,5]. Herein, we report a patient presenting with hydronephrosis-like manifestations due to a renal pelvic mass secondary to IgG4-RD.…”
Section: Introductionmentioning
confidence: 96%
“…This disease has only been recently proposed and is considered to involve systemic inflammatory fibrosis, including retroperitoneal fibrosis, autoimmune pancreatitis, chronic sclerosing sialadenitis and sclerosing cholangitis [1,2,3,4,5]. Herein, we report a patient presenting with hydronephrosis-like manifestations due to a renal pelvic mass secondary to IgG4-RD.…”
Section: Introductionmentioning
confidence: 96%
“…IgG4-related lesions have been further identified in other reports in such locations as the salivary gland [9], the lacrimal gland [10], the ocular adnexa [3], the pituitary gland [11], the pleura [12], the lung (interstitial pneumonia or inflammatory pseudotumor) [13], the breast (inflammatory pseudotumor) [14], the mediastinum (mediastinal fibrosis) [15], the pancreas (autoimmune pancreatitis) [16], the gallbladder [17], the bile duct [18], the liver (inflammatory pseudotumor) [19], the prostate [20,21], the retroperitoneum (retroperitoneal fibrosis) [22,23], the kidney (tubulointerstitial nephritis) [24], the aorta/artery (inflammatory abdominal aortic aneurysm) [25,26], the paravertebral area [27], the meninges [28], and the systemic lymph nodes (lymphadenopathy) [29]. Thus, it is likely that almost all organs can be affected in the IgG4-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have reported extra-pancreatic lesions associated with AIP, such as lachrymal and salivary [22,64], lung [26,27,[65][66][67][68], mediastinal [25], bile duct [8,28,69], renal [34,35,70,71], retroperitoneal [12] and prostatic [36][37][38] lesions. Recently, the concept of 'IgG4-related diseases' has been proposed because pathological findings similar to those of pancreatic lesion, more specifically infiltration of IgG4-bearing plasma cells, lymphocyte and fibrosis, were found in these extra-pancreatic lesions [2,12,22,33,[39][40][41][42].…”
Section: Extra-pancreatic Lesions Associated With Aip and Igg4-relatementioning
confidence: 99%
“…In addition, a variety of extra-pancreatic lesions, such as lachrymal and salivary gland lesions [22][23][24], hilar lymphadenopathy [24,25], interstitial pneumonia [24,26,27], sclerosing cholangitis [2,8,24,[28][29][30], retroperitoneal fibrosis [12,24,29,[31][32][33], renal lesions [24,34,35], and prostatic lesions [24,[36][37][38] have been reported to be complicated with AIP. Extra-pancreatic lesions show systemic distribution and share similar pathological and clinical findings with AIP, such as storiform fibrosis, prominent lymphoplasmacytic infiltration and abundant IgG4-bearing plasma cells [12,22,25,33], and have a favorable response to corticosteroid therapy [3, 4, 13-15, 22, 28-30].…”
Section: Introductionmentioning
confidence: 99%